Endovascular Management of Aorta-Iliac Stenosis and Occlusive Disease by Kissing-Stent Technique - Meng Liu; Fuxian Zhang (Stem Cells International)
Kissing-stenting treatment has been used to treat patients with peripheral artery disease (PAD). However, the long term efficacy of the stenting therapy is not well defined in Chinese PAD patients. To investigate the question, sixty-three PAD patients (37 males and 26 females), aged 66±7.3 years, were analysed in the study. They were featured as claudication (n=45, 71.4%), rest pain (n=18, 28.6%), or gangrene (n=8, 12.7%). In total, 161 stents were applied in aorta-iliac lesions with 2.6 stents for each patient, including 55 self-expanding stents, 98 balloon expandable stents, and 8 covered stents. The success rate of implanting Kissing-stents was 100%. Catheter-directed thrombolysis (CDT) with urokinase was performed in 8 cases (12.7%). The severity of peripheral ischemia was significantly improved, as evidenced by 3.3-fold increase of ankle-brachial pressure index (ABI) after the surgery (P=0.008). One, three, five, and seven years after surgery, the primary patency rate was 87.3%, 77.4%, 71.1%, and 65.0%, whereas the secondary patency rate was 95.2%, 92.5%, 89.5%, and 85.0%, respectively. No in-hospital mortality was recorded. In conclusion, Kissing-stenting technique for aorta-iliac lesions is safe and effective with lower complications. It is beneficial for aorta-iliac occlusions that are longer than 60 mm.